تحضير أفلام رقيقة نقية من بولي فينيل كلورايد PVC ودراسة تأثير سرعة الدوران على الثوابت الضوئية (Latakia University Journal -Basic Sciences Series, 2016)
In this research we have prepared thin films from poly vinyl chloride (PVC) by spin coating technique in three velocities (1000,2000,3000)RPM on glass substrate (Micro scope cover glass), at room temperature. The absorbance A, and transmittance T for the films were studied in the visible and ultra-violet region (UV-VIS). In addition,we have calculated the absorbance coefficient α, skin depth δ, refractive index no, dielectric constant ε (the real part and the imaginary part), also we have calculated the energy band gap of allowed and forbidden direct transitions. The films showed high transmittance (80-90)%, in the infrared region as a function of the spinning velocity and took the maximum value 80% for the velocity 1000RPM, and 90% for the velocity 3000RPM, and the refractive index was decreased with the velocity increase, we found it between3.67 and 4.56 for the velocities 3000RPM and 1000RPM respectively. Whereas the skin depth δ decreased with the increasing of velocity, the minimum value was 0.0000531cm for the velocity 3000RPM and the maximum value was almost 0.00023cm for the velocity 1000RPM.قمنا في هذا البحث بتحضير أفلام رقيقة نقية من بوليمير فينيل كلورايد PVC, بطريقة التغطية بالدوران (Spin Coating), من أجل ثلاث سرعات (1000,2000,3000)RPM, وذلك بترسيبها على قواعد زجاجية من النوع (Microscope cover glass) عند درجة حرارة الغرفة. درست الامتصاصية (Absorbance) و النفوذية (Transmittance) لهذه الأفلام في المنطقة المرئية وفوق البنفسجية (UV-VIS) للأشعة الضوئية. علاوة على ذلك قمنا بحساب معامل الامتصاص α(absorbance coefficient) وعمق النفاذ الضوئي للسطح δ(Skin Depth) ومعامل الانكسار (Reflectance coefficient) no,ومعامل العزل الكهربائي ε بجزأيه الحقيقي و التخيلي, وحسبنا أيضاً قيمة فجوة الطاقةEg للانتقالات الالكترونية المباشرة المسموحة منها والممنوعة.أظهرت الأفلام نفوذية عالية بحدود (80-90)%في مجال الأشعة تحت الحمراء وذلك بدلالة سرعة الدوران فبلغت الحد الأقصى 80% تقريباً بالنسبة للسرعة 1000RPM, و 90% تقريباً بالنسبة للسرعة3000RPMكما تناقصت قرينة الانكسارnoبازدياد سرعة الدورانحيث وجدنا أنها تتراوح بين3.67 و 4.56 عند السرعتين3000RPM و1000RPM على الترتيب في حين تناقص عمق النفاذ السطحي δبازدياد سرعة الدوران فكانت أصغر قيمة له 0.0000531cm عند السرعة 3000RPM, وأكبر قيمة له cm0.00023 عند السرعة 1000RPM.